Treatment of Duodenal Atresia with Kimura’s Diamond-Shaped-Duodeno-Duodenostomy (DSD) - Abid Hussain, Abdul Rehman, Tahir Mahmood Butt, Jehangir Khan, Abid Rafique Chaudhry, Muhammad Daraz Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Kimura’s diamond shaped duodeno-duodenostomy (DSD) is a well-recognized treatment for the management of duodenal atresia. Purpose: The aim of this study is to determine and share the experience of diamond shaped duodeno-duodenostomy and an overview of the benefits of this procedure. Place and Duration: In the Pediatric Surgery department of Govt. Sardar Begum Teaching Hospital Sialkot and Bacha Khan Medical Complex Swabi for five and half years from January 2016 to November 2021. METHODS: 42 neonates were surgically treated for duodenal atresia by Kimura’s technique. The transverse incision was given in the proximal dilated duodenum and longitudinal incision was given in the distal part of duodenum. Results: On 5th to 8 th day post-operatively, oral feeding was started (mean 6.2 days), full oral feeds were commenced between 7th to10th day (mean 9.2), peripheral intravenous fluids were discontinued 7th day to 10th day (mean 9.2), and hospital stay varies from 7th to 21st day (mean 10.8). The complications such as anastomosis leakage 1(2.4), infection 1(2.4), abnormal duodenal morphology 6(14.2) and Gastroesophageal reflux in 2(4.8) of patients. In prenatal ultrasonography of the fetus, obstruction of the duodenum was diagnosed in 31/42 (73.9%) and polyhydramnios in 19/42 (45.2%) cases. Conclusion: DSD offers a valuable technique to guard the ampulla of Vater from injury and blind loop can be avoided by this technique. The outcomes exhibited that patients of DSD attain complete per-oral nutrition in a very brief duration after surgery and subsequently the extent of hospital stay is reduced significantly.